1999
DOI: 10.1007/bf02349162
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of radionuclides with natural polyelectrolytes — proteins, polysaccharides and humic substances

Abstract: Various approaches to the modeling of metal and radionuclide interactions with macromolecular ligands, proteins, polysaccharides and humic substances in particular, their chemical and sorption equilibria, and the techniques used for their investigation are concisely compared. To predict radionuclide mobility in the natural and semi-natural aqueous environment, the estimation of the effective interaction constants, related to specific species of polyelectrolytes which are linked with the absorbancy or absorbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In studying sorption of Eu(III) using aromatic compounds, proteins, humic acids, and polysaccharides [6][7][8][9], it was found that the sorption capacity of these compounds is a function of the pH of the solution. High distribution coefficients in sorption of europium on chitin and chitosan were obtained in [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In studying sorption of Eu(III) using aromatic compounds, proteins, humic acids, and polysaccharides [6][7][8][9], it was found that the sorption capacity of these compounds is a function of the pH of the solution. High distribution coefficients in sorption of europium on chitin and chitosan were obtained in [10].…”
mentioning
confidence: 99%
“…These radionuclides are characterized by a long half-life and can cause long-term contamination. An analysis of the literature on methods of extracting Eu(III) from solutions using different sorbents [2][3][4][5][6][7][8][9][10] showed that the presence of phosphate groups in them increases the sorption efficacy [2,3]. In addition, we know that organophosphorus compounds (OPC) have been used for separating and removing rare-earth elements (REE) [4,5].…”
mentioning
confidence: 99%